Performance investigation of osmotic microbial fuel cell under different operational conditions: Effect of aeration mode, external resistance, and substrate concentrations - Hussein M. Abdelmohsen; Abdelsalam Elawwad (Desalination and Water Treatment)
Advancements in sustainable wastewater management require technologies that allow for simultaneous water treatment and resource recovery. Osmotic microbial fuel cells (OsMFCs) are a promising technology that merges forward osmosis (FO) with microbial fuel cells (MFCs). This study comprehensively assesses the impact of critical, yet under-explored, operational parameters—including aeration strategy, external resistance, and substrate concentration—on OsMFC efficiency. Initial results revealed a 15.3 % increase in power density compared to conventional MFCs, highlighting the importance of FO integration in bioenergy generation. There were also clear trade-offs in operational strategies: direct cathode aeration maximized energy recovery (2.67 W/m³) and COD removal (79 %), while unaerated conditions resulted in the greatest water flux (1.54 LMH) at the cost of lower electrical efficiencies. Several operational parameters were also optimized, including the COD load of the substrate (1500 mg/L), with polarization analysis suggesting that higher COD concentrations were associated with electrochemical and biological constraints that limit power output. Intermediate external resistance values (330 Ω) enabled peak power densities, while lower resistances allowed for enhanced Coulombic efficiency and water flux. This study also characterized the surface morphology of fresh, fouled, and chemically cleaned FO membranes. SEM, FTIR, and EDX analysis were used to identify key protein and polysaccharide foulants and assess the mitigation potential of cleaning procedures, providing insights into the sustainable, long-term operational viability of OsMFCs. This work establishes several key operational guidelines regarding aeration, external resistance, and substrate loading, and provides a practical foundation for advancing OsMFC technology toward efficient wastewater resource recovery.